2007
DOI: 10.1124/jpet.107.126409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Endogenous Ascorbate on Oxidation, Oxygenation, and Toxicokinetics of Cell-Free Modified Hemoglobin after Exchange Transfusion in Rat and Guinea Pig

Abstract: Chemically modified hemoglobin (Hb) solutions are promising oxygen therapeutics; however, these agents are prone to intravascular oxidation. Using a 50% exchange transfusion (ET) model with bovine polymerized hemoglobin (PolyHbBv), we examined heme oxidation, oxygenation markers, and toxicokinetics in rats, an ascorbic acid (AA)-producing species, and in guinea pigs, a non-AA-producing species. Plasma AA decreased by 50% in guinea pigs after ET, but it was unchanged in rats for the first 20 h post-ET. Both spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(127 citation statements)
references
References 32 publications
7
119
1
Order By: Relevance
“…Several animal studies have reported the accumulation of large quantities of oxidized Hb (ferric) (30–40%) after infusion of ferrous Hb or chemically modified Hb‐based oxygen carries (HBOCs) 30, 31. Recently it was shown that intravascular hemolysis in guinea pigs and beagle dogs (with acute kidney injury) led to intrarenal conversion of ferrous to ferric Hb, accumulation of free heme and Hb‐cross‐linked products, enhanced 4‐hydroxynonenal reactivity in renal tissue, and acute tubule injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have reported the accumulation of large quantities of oxidized Hb (ferric) (30–40%) after infusion of ferrous Hb or chemically modified Hb‐based oxygen carries (HBOCs) 30, 31. Recently it was shown that intravascular hemolysis in guinea pigs and beagle dogs (with acute kidney injury) led to intrarenal conversion of ferrous to ferric Hb, accumulation of free heme and Hb‐cross‐linked products, enhanced 4‐hydroxynonenal reactivity in renal tissue, and acute tubule injury.…”
Section: Discussionmentioning
confidence: 99%
“…While the redox reactions initiated at heme iron are well characterized from a chemical perspective, there is limited evidence that these reactions occur in vivo during hemolysis. Evaluating animal models of hemoglobinuria and exchange transfusion with a long circulating HBOC, we recently obtained evidence of globin and heme oxidative modifications, including oxidation of key β-chain amino acids and protein cross-linking, in animal blood and urine (9,30,57). Here, we found no evidence of heme oxidation within the circulation, as less than 2% of free intravascular Hb was observed in the oxidized Fe 3+ state and no Hb was observed in the higher oxidation ferryl (Fe 4+ ) state throughout the infusion time of up to 8 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The dog is therefore a unique model, in which the effects of intravascular Hb can be analyzed at a range of targeted endogenous Hp plasma concentrations. The guinea pig, on the other hand, allowed us to analyze both vascular and extravascular effects of extracellular Hb in the presence or absence of exogenously administered, purified human Hp in a nonascorbate-producing species, with blood and tissue antioxidant status comparable to that of humans (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disparity between in vitro biochemical observations and in vivo findings may be because of the shifted balance between oxidation and reduction reactions in in vivo conditions. 12 The availability of large quantities of small-molecule and enzymatic reductants may reduce the stability of higher-oxidation-state Hb species and Hb-derived radicals to undetectable levels. Intramolecular Hb cross-links, porphyrin-globin covalent adducts, and globin chain amino acid oxidations have been defined as surrogate markers for Hb-Fe 4ϩ formation.…”
Section: Mechanism 2: No and Oxidant Reactionsmentioning
confidence: 99%